Effectiveness of Premarital Counseling in Indonesia: Literature Review - Widodo, Rinto Wahyu; Manara, Muhammad Untung (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
This research aims to determine the picture of premarital counseling practices in Indonesia, which have developed over the past five years (2019-2023) as a trend. The research design uses a literature review because the researcher wants to review several articles published in scientific journals. The research instrument uses content analysis guidelines containing four main aspects: counseling model, type of counselee, counseling strategy, and counseling results. The researcher analyzed data by selecting several articles published in scientific journals using inclusion and exclusion criteria. After the researcher collected the articles, the quality of the articles, which contained four main aspects, was assessed and synthesized. An overview of premarital counseling practices in Indonesia shows that they use more group counseling models than individual counseling models. The counselees who take part in premarital counseling are more prospective brides and grooms than students, developmentally most of whom are in early adulthood with an age range of 18-40 years. The counseling strategy used is providing information. Therefore, this program can be called educational counseling. The results of premarital counseling have more influence on increasing the counselee’s knowledge, and this increase in knowledge has implications for the counselee’s readiness to face marriage.